Synthesis of bioplastics from selected fruit waste - Ong, Xin Shi (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Synthetic petroleum based plastics are used widely worldwide. They are basically made up of non-renewable resources such as petroleum and fossil fuels. Due to the increasing utilization of plastics in industry, there is a gradual increase in plastic waste accumulation since plastics are non-biodegradable. This phenomenon leads to a lot of environmental impacts such as global warming. Therefore, bioplastic as an alternative has been introduced to replace traditional synthetic plastic. Bioplastics are made up of renewable sources such as starch and cellulose which can be degraded and more eco-friendly. At the same time, there are large amount of food waste such as vegetable and fruit wastes were dumped worldwide every year. Therefore, food wastes are converted into reusable products such as bioplastics. Bioplastics can be classified into several types such as starch-based bioplastics, cellulose-based bioplastics, polyhydroxyalkanoate (PHA)/polyhydrxybutyrate (PHB) and Polylactic acid (PLA). In this project, bioplastics are produced directly from chosen fruit wastes through interaction with trifluoroacetic acid (TFA). One high starch fruit waste and four fruit wastes with high cellulose contents are chosen as raw materials in the production of amorphous cellulose-based plastics. Mango seed and pineapple crown fruit wastes with abundant cellulose content produced the best quality bioplastic films in terms of elongation, tensile strength and thermal stability whereas high starchy content fruit waste, banana peel produced highly brittle bioplastic film.